Pollinator Decline – An Ecological Calamity in the Making?. (June 2018) - Rhodes, Christopher J.
Since pollination by insects is vitally important for much of global crop production, and to provide pollination services more widely throughout the planetary ecosystems, the prospect of an imminent 'pollination crisis', due to a die-off of flying insects, is most disquieting, to say the least. Indeed, the term 'ecological Armageddon' has been used in the media. However, to know whether or not a wholesale decline in flying pollinators (including non-bee species) is occurring across the world is very difficult, due to an insufficiency of geographically widespread and long-term data. Bees, as the best documented species, can be seen to be suffering from chronic exposure to a range of stressors, which include: a loss of abundance and diversity of flowers, and a decline in suitable habitat for them to build nests; long-term exposure to agrochemicals, including pesticides such as neonicotinoids; and infection by parasites and pathogens, many inadvertently spread by the actions of humans. It is likely that climate change may impact further on particular pollinators, for example bumble bees, which are cool-climate specialists. Moreover, the co-operative element of various different stress factors should be noted; thus, for example, exposure to pesticides is known to diminish detoxification mechanisms and also immune responses, hence lowering the resistance of bees to parasitic infections. It is further conspicuous that for those wild non-bee insects – principally moths and butterflies – where data are available, the picture is also one of significant population losses. Alarmingly, a recent study in Germany indicated that a decline in the biomass of flying insects had occurred by 76% in less than three decades, as sampled in nature reserves across the country. Accordingly, to fully answer the question posed in the title of this article 'pollinator decline - an ecological calamity in the making?' will require many more detailed, more geographically encompassing, more species-inclusive, and longer-term studies, but the available evidence points to a clear 'probably', and the precautionary principle would suggest this is not a prospect we can afford to ignore.